1997
DOI: 10.1046/j.1365-2958.1997.2071571.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a mitogen‐activated protein (MAP) kinase from Plasmodium falciparum

Abstract: SummaryA mitogen-activated protein (MAP) kinase gene, PfMAP, from Plasmodium falciparum was recently identified. We expressed this gene in Escherichia coli to test whether it encodes a functional MAP kinase. Recombinant PfMAP kinase autophosphorylates on both the tyrosine and threonine residues within the TXY motif, and readily phosphorylates myelin basic protein as exogenous substrate. This identifies the PfMAP gene product as a true member of the growing family of MAP kinases. Wild-type PfMAP kinase expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
1
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 34 publications
2
27
1
3
Order By: Relevance
“…Despite the presence of two MAPK-encoding genes, Pfmap-1 (6,12,15) and Pfmap-2 (7), the P. falciparum genome does not possess orthologues of the MAPK kinase (also called MEK, for MAP/ERK kinase) family (1,28), raising the question of the mode of activation of Pfmap-1 and Pfmap-2. PfPK7 (PlasmoDB database identifier PFB0605w) is the P. falciparum enzyme with the highest level of homology to MEKs (8).…”
mentioning
confidence: 99%
“…Despite the presence of two MAPK-encoding genes, Pfmap-1 (6,12,15) and Pfmap-2 (7), the P. falciparum genome does not possess orthologues of the MAPK kinase (also called MEK, for MAP/ERK kinase) family (1,28), raising the question of the mode of activation of Pfmap-1 and Pfmap-2. PfPK7 (PlasmoDB database identifier PFB0605w) is the P. falciparum enzyme with the highest level of homology to MEKs (8).…”
mentioning
confidence: 99%
“…Use of immunoblot analysis and immunopreciptation reaction has allowed revealing in P. falciparum four different MAP kinase forms: p40, p80, p100, and p150 (Lin et al, 1996, Graeser et al, 1997. The total MAP kinase activities increased in the process of parasite maturation (Graeser et al, 1997). Activity of the p80 kinase was high at the asexual stage of parasite development, whereas the p100 protein activity, on the contrary, in gametes and zygote.…”
Section: Pkc1mentioning
confidence: 99%
“…A MAPK homologue of Plasmodium falciparum, PfMAP (also known as Pfmap-1), was simultaneously discovered independently in three laboratories (Doerig et al, 1996;Lin et al, 1996;Graeser et al, 1997). It was shown that, like other MAP kinases, it contained a TXYmotif in the kinase subdomain VIII, whose phosphorylation at tyrosine and threonine is essential for activity (Robbins et al, 1993;Graeser et al, 1997).…”
Section: Pkc1mentioning
confidence: 99%
See 2 more Smart Citations